International politics of HIV/AIDS : global disease - local pain - Seckinelgin, Hakan; Hakan Seckinelgin, RefineCatch Limited, Bungay, Suffolk, TJ International Ltd, Padstow, Cornwall (London ; New York : Routledge, 2008)
"This book examines the global governance of the HIV/AIDS epidemic, interrogating the role of this international system and global discourse on HIV/AIDS interventions. The geographical focus is Sub-Saharan Africa since the region has been at the forefront of these interventions. There is a need to understand the relationship between the international political environment and the impact of resulting policies on HIV/AIDS in the context of people's lives. The book points out a certain disjuncture between the governance structures and the way people experience the disease in their everyday lives."--Jacket.
Includes bibliographical references (pages 170-186) and index.
Adult
Keywords: South Africa